Second Cluster of the Baroli Group of Temples - Temples of India Project Team (Jio Institute, 2024)
The second cluster in the Baroli group of temples includes Ghateshwar Temple, Mahishasuramardini Temple, Vamana Temple and Sadashiva Temple. There is also a detached big doorframe, a kund (tank), a small modern shrine and a series of Shiva lingas (arranged in raw) in this cluster.